(untitled) (Third Sector Social Economic Review, 2018)
The purpose of this study was to investigate the relationship between the OCB and organizational silence and to determine the effects of the sub-dimensions of organizational silence on the OCD. For thisreason, a field study was conducted on the public employees of Karaman province. As a result of the study, a positive relationship was found between the OCB and organizational silence. There was also no difference between demographic characteristics such as marital status, trade union membership, status, age, education and income status and the dependent variable. Only gender and duration of study were found to be effective on OCB.